Tingkat Keberhasilan Kegiatan Pengayaan Pada Program Rehabilitasi Hutan Dan Lahan Di Taman Hutan Raya Pocut Meurah Intan, Aceh - OK Hasnanda Syahputra; Maryam Jamilah; Syifa Saputra (Jurnal Lingkungan Almuslim, 2022)
This study aims to evaluate the success of enrichment activities in the National Movement for Forest and Land Rehabilitation program that has been carried out at the Technical Implementation Unit of the Pocut Meurah Intan Forest Park Forest Management Unit. Plant observations were carried out using the Systematic Sampling with Random Start method, with a sampling intensity of 5% or a research area of 5 Ha from a 100 ha enrichment area. The experimental parameters are the type composition, the number of plants, and the state of health of the plant. The results of field observations found that the design of plant types was six: three types of cash plants and three types of Multiple Purpose Tree Species (MPTS). Jackfruit (Artocarpus Integra) is the most dominant growing plant. At the same time, Meranti (Shorea sp) is the plant that grows the least. There were 757 plant stems from the entire plot, with a growing percentage of 37.85% and a healthy percentage of 34.80%. The failure of planting in this program is due to the lack of community involvement in preparing plans for these activities, the lack of continuous supervision, and the timing of implementation does not correspond to the growing season.